DESKRIPSI UPAYA GURU DALAM MENINGKATKAN LITERASI MEMBACA SISWA SD - Ermanza, Chelsi; Darusman, Hafizah; Varadisi, Reza; Rahma, Alifina; Suriani, Ari; Syam, Salmaini Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading literacy is a fundamental competence that supports students’ learning success in elementary schools. However, students’ reading literacy skills have not developed optimally, as indicated by low reading comprehension and reading interest. This study aims to describe teachers’ efforts in improving students’ reading literacy in elementary schools. The research employed a qualitative approach with a descriptive design through a literature study. Data were collected from various relevant sources, including scientific journals, books, and previous research findings, and were analyzed using content analysis techniques. The findings reveal that low reading literacy is influenced by internal factors, such as low motivation and reading interest, as well as external factors, including limited reading resources, lack of variation in teaching methods, and the underdeveloped literacy culture in schools and families. Teachers play a strategic role as facilitators, motivators, and guides in improving reading literacy through reading habituation programs, innovative learning methods, and the creation of literacy-supportive learning environments. Therefore, continuous and integrated efforts involving teachers, schools, and families are necessary to improve students’ reading literacy skills effectively.